2005
DOI: 10.1074/jbc.m505994200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Minimal Lysosomal Enzyme Recognition Domain in Cathepsin D

Abstract: Specific recognition of lysosomal hydrolases by UDP-GlcNAc:lysosomal enzyme N-acetylglucosamine-1-phosphotransferase, the initial enzyme in the biosynthesis of mannose 6-phosphate residues, is governed by a common protein determinant. Previously, we generated a lysosomal enzyme recognition domain in the secretory protein glycopepsinogen by substituting in two regions (lysine 203 and amino acids 265-293 of the ␤ loop) from cathepsin D, a highly related lysosomal protease. Here we show that substitution of just … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 16 publications
0
30
0
Order By: Relevance
“…The minimum number of substitutions needed to generate a recognition motif was two lysines at the correct positions (22). However, the binding signal was substantially enhanced by the substitution of additional residues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The minimum number of substitutions needed to generate a recognition motif was two lysines at the correct positions (22). However, the binding signal was substantially enhanced by the substitution of additional residues.…”
Section: Discussionmentioning
confidence: 99%
“…In prior studies we have generated a GlcNAc-1 phosphotransferase protein recognition motif in the secretory protein pepsinogen by substituting elements from the related aspartic protease cathepsin D into equivalent positions of pepsinogen (22,26,35,40). The minimum number of substitutions needed to generate a recognition motif was two lysines at the correct positions (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies from our laboratory and others have shown that the protein recognition domain of acid hydrolases is a complex conformation-dependent determinant that includes a number of critical lysine residues (16)(17)(18)(19)(20)(21)(22)(23). On this basis, it seems likely that the interaction of an acid hydrolase with GlcNAc-1-phosphotransferase would involve multiple contacts between the surfaces of the two proteins.…”
mentioning
confidence: 99%
“…The determination of the percentage of latent TGF-␤1 glycans that are Man-6-Pmodified was performed as described earlier but without ammonium chloride in the culture medium (33)(34)(35). The percentage phosphorylation was calculated as the radioactivity (cpm) recovered in Endo H f -released glycans with one or two phosphates/total cpm in Endo H f -released glycans ϩ 2 Endo H f -resistant complex glycans.…”
Section: -3 H]mannose Labeling and Analysis Of Mannose Phosphorylatimentioning
confidence: 99%